Discriminatory job advertisements for English language teachers in Colombia: An analysis of recruitment biases. Issue 1 (2nd July 2020) - Mackenzie, Lee
Abstract: Numerous studies have explored the persistence of discrimination against nonnative‐English‐speaking teachers (NNESTs) of English as a foreign or second language in various contexts. However, the author of this article could find no study that explores the prevalence of "native‐speakerism" and other forms of discrimination in English language teacher recruitment in South America. The current study thus investigated the extent to which online postings for English language teachers in Colombia expressed a preference for native‐English‐speaking teachers (NESTs) and how this discrimination intersects with other inequitable hiring practices. The author conducted content analysis on job ads found on two prominent Facebook groups for English language teachers in Colombia. The findings reveal evidence of discrimination in nearly half of the 95 job ads analysed. These ads discriminate based on age, gender, nationality, variety of English, the location where a prospective teacher gained their qualifications, and "nativeness." The study tentatively concludes that this discrimination has several dimensions, with those further from the colonial "centre" facing greater degrees of discrimination. The mutually reinforcing constructs of coloniality and native‐speakerism help account for the persistence of such discrimination, which is also reflected in the Colombian governments' linguistic policies.